Parametryzacja, humanistyka i los mieszkańców Rapa Nui = Parametrization, the humanities, and the fate of the people from Rapa Nui - Chutorański, Maksymilian; Szwabowski, Oskar (Zielona Góra: Lubuskie Towarzystwo Naukowe)
In this article, parameterization is accounted for as part of the neoliberal academy ma management. Taking as a starting point the accepted understanding of the role of the humanities, the authors put forward the thesis that parameterization cannot be the main mechanism for stimulating scientific development. Developing the above-mentioned issues, the authors justify the need for academic utopianism capable of rethinking the essence and meaning of the practice of evaluating researchers.
Keywords: uniwersytet; parametryzacja; utopistyka akademicka; university; parametrization; academic utopianism